2020
DOI: 10.1007/s10802-020-00703-x
|View full text |Cite
|
Sign up to set email alerts
|

Unpacking Associations between Mood Symptoms and Screen Time in Preadolescents: a Network Analysis

Abstract: Funding. There is no funding to report for the present work. Conflicts of interest/Competing interests. There is no conflict of interests to report for the present work. Availability of data and material. The current study was based on de-identified open datasetsthe Adolescent Brain and Cognitive Development (ABCD) Study. The usage did not require IRB approval. Code availability. The current analyses were conducted based on open-source R packages, including qgraph, mgm, bootnet, and NetworkComparisonTest.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 86 publications
2
4
1
Order By: Relevance
“…For the PSU community, the two strongest positive edges were between PSU1 “salience” and PSU3 “mood modification” and between PSU4 “tolerance” and PSU6 “relapse”; this has also been found in a prior network research ( 24 ). The three strongest edges found within the BIS/BAS community are similar to the results found by other studies using network analysis ( 94 ). They were between BASD “BAS-drive” and BASF “BAS-fun seeking,” between BASR “BAS-reward responsiveness” and BASF “BAS-fun seeking,” and between BASR “BAS-reward responsiveness” and BASD “BAS-drive.” For the impulsivity community, the strongest edge was between I1 “non-planning impulsivity” and I 3 “attentional impulsivity,” which is consistent with prior studies that revealed a positive correlation between non-planning impulsivity and attentional impulsivity ( 95 ).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…For the PSU community, the two strongest positive edges were between PSU1 “salience” and PSU3 “mood modification” and between PSU4 “tolerance” and PSU6 “relapse”; this has also been found in a prior network research ( 24 ). The three strongest edges found within the BIS/BAS community are similar to the results found by other studies using network analysis ( 94 ). They were between BASD “BAS-drive” and BASF “BAS-fun seeking,” between BASR “BAS-reward responsiveness” and BASF “BAS-fun seeking,” and between BASR “BAS-reward responsiveness” and BASD “BAS-drive.” For the impulsivity community, the strongest edge was between I1 “non-planning impulsivity” and I 3 “attentional impulsivity,” which is consistent with prior studies that revealed a positive correlation between non-planning impulsivity and attentional impulsivity ( 95 ).…”
Section: Discussionsupporting
confidence: 88%
“…For the PSU community, the two strongest positive edges were between PSU1 "salience" and PSU3 "mood modification" and between PSU4 "tolerance" and PSU6 "relapse"; this has also been found in a prior network research (24). The three strongest edges found within the BIS/BAS community are similar to the results found by other studies using network analysis (94). They were between BASD "BAS-drive" and BASF "BAS-fun seeking, " between BASR "BAS-reward responsiveness" and BASF "BAS-fun seeking, " and between BASR "BAS-reward responsiveness" and BASD "BASdrive."…”
Section: Discussionsupporting
confidence: 85%
“…Despite some research combining a variety of screen-based activities into one screen time variable (Lin et al, 2020;Oberle et al, 2020), the differences across TV viewing, Internet use, text messaging, and video game playing in the present study indicated that an aggregate score was unsuitable. The correlations among the screen time variables were inconsistent, ranging from negligible to approaching moderate magnitudes.…”
Section: Variability In Screen Timecontrasting
confidence: 69%
“…Students with missing responses for the loneliness variables may be at higher risk of loneliness, although the use of passive consent protocols is shown to encourage more robust reporting of sensitive areas among youth and preferable student representation/response rates (Chartier et al, 2008; White et al, 2004). Use of the single loneliness item is recommended for large scale surveys (Office for National Statistics, 2018), and has been shown to be a significant indicator of emotional loneliness, which focuses on the intimacy of one's relationships, rather than the size of one's social network (Lin et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found a signi cant positive relationship between depressed mood and substance and alcohol use among adults [11][12][13]. Furthermore, a growing body of evidence highlights that substance use and heavy consumption of alcohol among adults has been associated with stressful life experiences ,as many may tend to consume excessive alcohol as act of coping with negative feelings [14,15].…”
mentioning
confidence: 99%